A discourse on structure of acknowledgments in doctoral dissertation in a multiracial setting - Nurul Nadwa Ahmad Zaidi,; Wan Nurul Fatihah Wan Ismail,; Muhd Syahir Abdul Rani,; Wan Najmu’deen Wan Omar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The existence of acknowledgment in academic paper has become an academic practice. This paper explores the generic structure of doctoral dissertation acknowledgments of three major races in Malaysia through discourse analysis. It also aims to find differences of the moves and steps used by the three races. Fifty samples from each race were selected based on their availability from local and foreign universities. The fundamental moves and steps were scrutinised and documented in the categories of the collected acknowledgements. The findings of the study disclosed that the structural arrangement of doctoral dissertation acknowledgements has the same structure with the arrangement of Arab dissertation acknowledgements. However, there is no vast difference of acknowledgement writing between the three races. From the findings, this study comes out with a modified model of generic structure of doctoral dissertation acknowledgements. The findings of this paper might be of interest to genre analysts as well as to second language theorists and practitioners even though it was done on small corpora. Based on the outcome of this paper, it is suggested that future study is carried out to determine the effects of academic disciplines differences in writing acknowledgements of doctoral dissertation.